2022
DOI: 10.3390/ijms232113187
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Low-Nitrogen-Related miRNAs and Their Target Genes in Sugarcane and the Role of miR156 in Nitrogen Assimilation

Abstract: Chemical nitrogen (N) fertilizer is widely used in sugarcane production, especially in China and India. Understanding the molecular mechanisms and mining miRNAs and their target genes associated with nitrogen use efficiency (NUE) in sugarcane can aid in developing the N-efficient varieties, and thus is beneficial to reduce N fertilizer application. In this study, the root miRNA database of N-efficient sugarcane variety ROC22 under low N stress (0.3 mM NH4NO3) for 3 h was constructed, along with their transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…A long intergenic noncoding RNA (lincRNA) with significant complementarity to miR408 was predicted to act as miRNA bait, with inhibitory effects on the regulation of canonical miR408 targets (Thiebaut et al, 2017). Other studies showed that miRNAs influence sugarcane growth and development, stress resistance, and other processes Gao et al, 2022). The research conducted to date on sugarcane lncRNAs has primarily relied on predictions, which will need to be experimentally verified.…”
Section: Sugar Cropsmentioning
confidence: 99%
“…A long intergenic noncoding RNA (lincRNA) with significant complementarity to miR408 was predicted to act as miRNA bait, with inhibitory effects on the regulation of canonical miR408 targets (Thiebaut et al, 2017). Other studies showed that miRNAs influence sugarcane growth and development, stress resistance, and other processes Gao et al, 2022). The research conducted to date on sugarcane lncRNAs has primarily relied on predictions, which will need to be experimentally verified.…”
Section: Sugar Cropsmentioning
confidence: 99%
“…The expression of the H 2 O 2 -responsive miR156 [100] was affected by low light intensity, red, far-red, and blue light [142,148,149]. Overexpressing of sugarcane miR156 in Arabidopsis up-regulated key genes of nitrate reduction and amino acid synthesis (GLUTAMINE SYN-THASE) [157], for which processes the modulating effect of light intensity, blue, red, and far-red spectral components was shown in wheat [67]. Certain amino acids, in turn, affect the redox homeostasis through their involvement in the formation of GSH (Cys, Glu, Gly) or the consumption/production of reducing power during their metabolism (for instance Pro-NADPH); therefore, feedback control may function for the light-dependent modulation of nitrogen metabolism by miR156 and the redox system.…”
Section: Light-dependent Interaction Between the Redox System And Mirnasmentioning
confidence: 99%